Assessment of basin-scale geomorphic processes based on the analysis of longitudinal profiles: A case study of the Dwarkeswar river, Eastern India - Biman Ghosh (Geology, Ecology, and Landscapes)
The longitudinal profile of the river bears geomorphic signature of long-term fluvial adjustment to tectonic, structure, lithology, and climate. Therefore, analysis of the longitudinal profile can be helpful in understanding the fluvial process and the response of the river to regional geodynamics. The present study uses longitudinal profiles and related geomorphic indices, including the Stream Length-Gradient Index (SL Index) of the Dwarkeswar river and its nine major tributaries, to understand the role of regional geological structure and lithology on the landscape evolution of the basin and the stage of river-valley development. Four mathematical functions were used in the present study to fit the curves of the profiles, on the basis of which the sequence of evolution was estimated. The exponential function is the best fit, followed by the linear function for each river, indicating a dynamic equilibrium condition. Moreover, profile concavity and hypsometric integral were used in the present study to understand sediment generation and transportation dynamics. The lower concavity index in Arkasa, Beko river, and Debkhal rivers indicate that sediment production and transportation balance each other. All the indices and the shape of Hack’s profile indicate that the rivers are in non-graded condition. The concavity of the profile reveals that Dwarkeswar rivers is an energy-limited river with a lower sediment delivery ratio (SDR)(0.47). Other rivers of the basin have moderate to high SDR (0.61–0.78). The integration of the results with the geological data indicates that the segments with anomalously high values of the SL index correspond to the fault lines, lineaments, and lithological discontinuities.